Documenting informal and customary land rights in Africa Challenges of using participatory means - Kealeboga Kaizer Moreri (African Journal on Land Policy and Geospatial Sciences, 2020)
The adoption of modern Land Administration Systems (LAS) in Sub Saharan Africa is done with the expectation that principles of equity, non-discrimination, efficiency, transparency, productivity and sustainability among others may be achieved to meet societal needs in those countries.  However, a lack of functional systems to document land through the provision of proper documentation particularly in Sub Saharan Africa has led to a high tenure insecurity in local communities, landlessness and a lack of proper investment in the land they hold. This study designed a typology that highlights key challenges of administering informal and customary land in five countries from different regions of Sub Saharan Africa regarded as leaders in land administration. Moreover, it proposes five innovative parameters for addressing the challenges of documenting informal and customary land rights using participatory means, such that governments can establish LAS that best meet the need of local communities.